Quantification of 15 Antibiotics Widely Used in the Critical Care Unit with a LC-MS/MS System: An Easy Method to Perform a Daily Therapeutic Drug Monitoring - Catherine Feliu; Celine Konecki; Tristan Candau; Damien Vautier; Cyril Haudecoeur; Claire Gozalo; Yoann Cazaubon; Zoubir Djerada (MDPI AG, 2021)
Potential under- or overdose of antibiotics may occur in intensive care units due to high variability in plasma concentrations. The risk is either treatment failure or toxicity. Thus, therapeutic drug monitoring of antibiotics may guide dosing adjustment, maximising antibacterial efficacy and minimising toxicity. The aim of this study was to develop and validate a method for the analysis of 15 antibiotics including beta-lactams, linezolid, fluoroquinolones, daptomycin, and clindamycin to have a complete panel in the management of infections. We proposed to develop a fast, sensitive, and quantitative method for the analysis of 15 antibiotics using ultra-performance liquid chromatography coupled with triple quadrupole mass spectrometer (UPLC-MS/MS) technology. this method required only 100 µL of plasma and consisted of a rapid liquid-liquid deproteinisation using methanol. Calibration curves ranged from 0.078 to 500 mg/L depending on the molecules, and were defined according to a therapeutic range. Inter- and intra-assay precisions values were less than 15%. This work described the development and the full validation of a precise, sensitive and accurate assay using UPLC-MS/MS technology. After validation, this new assay was successfully applied to routine therapeutic drug monitoring.